Metaverso como novo paradigma de mercado: avaliação do potencial do ambiente virtual para experiências de consumo e interação com produtos - Calmont, Ester Figueiredo da Silva (Brasil, 2024)
The Metaverse represents a shared virtual reality that is emerging with the possibility of providing opportunities in diverse sectors, including entertainment, education and commerce. With the emergence of new technologies, it has become essential to encourage discussion about the use of the Metaverse and its ramifications, while at the same time establishing a question so that researchers and academics can deepen their investigations on the subject. Therefore, the study in question aimed to evaluate the Metaverse as a new paradigm of the digital market and consumption. In the meantime, quantitative research was carried out, involving 108 diverse participants, aiming to capture a variety of perspectives in a broad context. The results showed a growing interest and readiness to explore this emerging digital dimension, although there are also critical stances towards the Metaverse, carefully considering both its potential benefits and its risks.